Improving Cell Engraftment in Cardiac Stem Cell Therapy - Xiaofei Li; Kenichi Tamama; Xiaoyun Xie; Jianjun Guan (Hindawi Limited, 2016)
Myocardial infarction (MI) affects millions of people worldwide. MI causes massive cardiac cell death and heart function decrease. However, heart tissue cannot effectively regenerate by itself. While stem cell therapy has been considered an effective approach for regeneration, the efficacy of cardiac stem cell therapy remains low due to inferior cell engraftment in the infarcted region. This is mainly a result of low cell retention in the tissue and poor cell survival under ischemic, immune rejection and inflammatory conditions. Various approaches have been explored to improve cell engraftment: increase of cell retention using biomaterials as cell carriers; augmentation of cell survival under ischemic conditions by preconditioning cells, genetic modification of cells, and controlled release of growth factors and oxygen; and enhancement of cell survival by protecting cells from excessive inflammation and immune surveillance. In this paper, we review current progress, advantages, disadvantages, and potential solutions of these approaches.